2013
DOI: 10.1186/1471-2334-13-610
|View full text |Cite
|
Sign up to set email alerts
|

Aedes aegyptifrom temperate regions of South America are highly competent to transmit dengue virus

Abstract: BackgroundAedes aegypti is extensively spread throughout South America where it has been responsible for large dengue epidemics during the last decades. Intriguingly, dengue transmission has not been reported in Uruguay and is essentially prevalent in subtropical northern Argentina which borders Uruguay.MethodsWe assessed vector competence for dengue virus (DENV) of Ae. aegypti populations collected in subtropical Argentina (Corrientes) as well as temperate Uruguay (Salto) and Argentina (Buenos Aires) in 2012 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
19
1

Year Published

2014
2014
2025
2025

Publication Types

Select...
5
4
1

Relationship

2
8

Authors

Journals

citations
Cited by 25 publications
(20 citation statements)
references
References 29 publications
0
19
1
Order By: Relevance
“…In Uruguay, a few Ae. albopictus were once detected near the Brazilian border, however subsequent efforts have failed to confirm the colonisation of the country by this species ( apud Lourenço-de-Oliveira et al 2013 ). Similarly, the occurrence of this mosquito in Bolivia, in South America, as previously suggested as infested by Benedict et al (2007) , has never been confirmed.…”
Section: Discussionmentioning
confidence: 99%
“…In Uruguay, a few Ae. albopictus were once detected near the Brazilian border, however subsequent efforts have failed to confirm the colonisation of the country by this species ( apud Lourenço-de-Oliveira et al 2013 ). Similarly, the occurrence of this mosquito in Bolivia, in South America, as previously suggested as infested by Benedict et al (2007) , has never been confirmed.…”
Section: Discussionmentioning
confidence: 99%
“…Equation (4) represents the infectiousness of a host with parasitemia, n , for a feeding vector. Note that equation (4) depends on two parameters (λ 1 , λ 2 ), which vary according to vector, host, disease type, and environmental parameters (e.g., temperature) [20] . This equation is our key result since it enables the calculation of the HIP from the distribution of host parasitemias.…”
Section: Methodsmentioning
confidence: 99%
“…Fully engorged females were transferred to cardboard cups and maintained on 10% sucrose in climatic chambers (KB 53, Binder, Tuttlingen, Germany) set at constant temperatures of 208C + 0.18C or 288C + 0.18C, with a 16 L : 8 D cycle and 70% relative humidity. A temperature of 208C was chosen as representative of the low-temperature threshold recorded when local CHIKV transmission occurred during the Italian epidemic between June and September 2007 [21,25] and in southeast France in September 2010 (http://www.meteociel.fr) [23], whereas 288C was chosen as a typical average temperature in tropical regions and has been commonly used in CHIKV vector competence assays [19,[26][27][28][29].…”
mentioning
confidence: 99%